A Report of Two Cases of Age-Related Changes in Cervical Morphology in Postmenopausal Women with Vaginal Adenosis. (2nd January 2017) - Vigliani, Marguerite B.
Abstract : This paper presents two cases of women who had extensive vaginal adenosis from prenatal DES exposure, extending almost halfway down the vaginal canal. Both women were followed for decades with annual exams and Pap smears until after menopause. Clinical examination in both cases initially showed an absent pars vaginalis of the cervix, vaginal adenosis, and shallowness of the fornices. Several decades of annual exams showed these stigmata of DES exposure gradually disappear as the upper vagina progressively contracted. After menopause the upper vagina in both cases transformed into what appeared to be a normal cervix with all adenosis involuted into a normal endocervical canal. A timeline was created to show the morphological changes that were observed over time. This timeline illustrates how severe vaginal stenosis above the level of the squamocolumnar junction developed in middle age and was followed in the postmenopause by fusion of the upper vaginal walls in the midline resulting in the appearance of a normal, but prolapsed, cervix.